Science experiments with light - Nankivell-Aston, Sally; Jackson, Dorothy (London Franklin Watts, 2007)
Explores the properties of magnets through experiments using equipment readily available in both homes and schools.
Includes index.
Keywords: Magnetism -- Experiments -- Juvenile literature; Magnetism -- Experiments; Experiments